Steve Farrah, Not Black, Not White: The Politics of Apartheid in South Africa: An extremely problematic account (Historia, 2021)
The sub-title of this book is misleading in that it does not deal with the politics of apartheid in any systematic way but is rather a memoir recounting the experiences of the author, which are contextualised within a description of the apartheid system. His classification as coloured under the Population Registration Act explains the "Not Black, Not White" in the naming of the book. Farrah, who was born in the mid 1920s and lived in Johannesburg for most of his life, entered the teaching profession as a young man. He taught at Alexandra Primary School from 1946 to 1956 and upon gaining his masters degree was transferred to Coronationville High School, where he eventually became principal in 1968. He was extensively involved in coloured teacher organisations, serving for more than a decade as general secretary of the Transvaal Association of Teachers and became vice-president of the South African Federation of Teachers' Associations in the early 1970s. Farrah emigrated to the United States in 1979 where he became an American citizen in 1986. He has been living in Phoenix, Arizona and taught English at secondary school level until his retirement in 1997.